Modern Mathematics - Wongpinit, Weerapong; Meksawang, John (SciTech Research Journal, 2019)
Mathematics has become an important role to study and investigate the knowledge in both sciences and social sciences. Development of knowledge in almost branch need of the new mathematical principle ever time. This article aimed to study modern of mathematics and to learn, understand, accept and adapt up to date world. The study results were as follows: The study of modern mathematics is to study as the structure of mathematics which contains undefined terms, defined terms, and axioms and then use the logical reasoning to prove theorem, rule or formula for application in the real world. The main concepts of modern mathematics are generalization, abstraction and arithmetization, respectively.